2004
DOI: 10.1002/ffj.1292
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils of Lantana camara L. occurring in south China

Abstract: Steam-distilled volatile oils from the leaves and flowers of Lantana camara L. were analysed by GC and GC-MS. The oils are characterized by a high percentage of sesquiterpenes. The main components detected are germacrene D (15.85%), β-caryophyllene (12.35%), α-humulene (9.31%) and germacrene-B (6.19%). 1,8-Cineole (4.61%), an oxygenated monoterpene is also reported. Experimental Plant Material and Extraction of VolatilesAerial parts of L. camara were collected from the campus of South China Agricultural Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 24 publications
3
15
1
1
Order By: Relevance
“…The germacrene-D was present in some EOLC analyzed (Sundufu & Shoushan, 2003;Da Silva et al, 1999;Khan et al, 2002) and the cariophylene groups were observed to be the only versatile components present in every EOLC analyzed by different authors (Ngassoum et al, 1999;Sefidkon, 2002;Rana, 2005), which is confirmed by the present work.…”
Section: Resultssupporting
confidence: 89%
“…The germacrene-D was present in some EOLC analyzed (Sundufu & Shoushan, 2003;Da Silva et al, 1999;Khan et al, 2002) and the cariophylene groups were observed to be the only versatile components present in every EOLC analyzed by different authors (Ngassoum et al, 1999;Sefidkon, 2002;Rana, 2005), which is confirmed by the present work.…”
Section: Resultssupporting
confidence: 89%
“…10;2012 (3.22%), calarene (3.19%), ∆-cadinene (2.9%), α-pinene (2.11%) and trans-sabinene (1.09%). These results were in agreement with most published data like the South Chinese essential oil revealed by Sundufu and Shoushan (2004) where they found almost exact α-humulene (9.3%), higher 1,8-cineol (4.6%), lower sabinene (1.1%), lower α-pinene (0.8%), lower isomer β-caryophyllene (13.35%) and dominant higher germacrene D (15.9%) also higher germacrene D was found in other studies (da Silva et al, 1999;Möllenbeck et al, 1997). Recent study in Algeria reported that β-caryophyllene was dominant (35.7%) and lower α-humulene (3.72%), in L. camara oil (Zoubiri & Baaliouamer, 2011).…”
Section: Chemical Composition Of the Essential Oilssupporting
confidence: 93%
“…Essential oils such as β-caryophyllene, δ-cadinene, epi-α-cadinol and α-cadinol have also been isolated from the A. muricata plant (Pelissler et al, 1994;Kossouoh et al, 2007). Some essential oil like beta-caryophyllene present in other plants have been reported to exhibit hypotensive and vasodilator activities (Damiani et al, 2004;Sundufu & Shoushan, 2004;Morteza-Semnani, 2006;Kamboj & Saluja, 2008) and the presence of such compounds in A. muricata might possibly contribute to the cardiovascular effects observed with the aqueous plant extract (Abdalla et al, 1995).…”
Section: Discussionmentioning
confidence: 99%